COMPETITIVENESS MODELING AND SWOT STRATEGY ANALYSIS FOR TOURISM INDUSTRY IN EAST JAVA - Hermawati, Adya; Suhermin, Suhermin (Universitas Brawijaya, Indonesia, 2020)
The objective of this research is to identify the internal and external conditions of the tourism industry in East Java and also to find out the appropriate competitiveness model for this industry. Indicators in the questionnaire are proved to be valid in measuring competitiveness. It is found that each indicator has a significant effect on competitiveness. Strategically, it is identified that internal and external conditions of the tourism industry have high strength and high opportunity for supporting the Indonesian economy. The result of the preliminary study shows that not many previous researches are discussing how to improve the competitiveness of the tourism industry in East Java.